THE EFFECT OF BACKWARD CHAINING METHOD ON SELF-HELP SKILLS OF CEREBRAL PALSY CHILDREN - Elsa Dikeu Septiani (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This study aims to determine the effect of applying the backward chaining method on the ability of children with cerebral palsy at SKh Agrowisata to dress themselves using this method. The type of research used is Single Subject Research (SSR). The design used is A- B-A design. The research subject is a grade II student of SKh Agrowisata who has difficulty in his motor skills so that it affects his daily activities, especially in terms of dressing. Data were collected through observation and analysis. Based on the results of the study, the subject received an average presentation or average level in the initial condition / baseline- 1 (A1) obtained the results of 25, 25% where in this phase in the natural condition of the subject, then in the intervention phase (B) the subject was given intervention or treatment in the form of applying the backward chaining method by obtaining a value of 93.3% and in the final condition / baseline-2 (A2) obtained a value of 70.8%. The percentage of overlapping data in the intervention phase (B) is 0%. Thus, it can be concluded that the application of the backward chaining method can improve the ability of self-help dressing skills for children with cerebral palsy class II SKh Agrowisata